Yin Yang 1-induced activation of LINC01133 facilitates the progression of pancreatic cancer by sponging miR-199b-5p to upregulate myelin regulatory factor expression. Issue 5 (2nd May 2022) - Yang, Xi; Wang, Leiming; Zhou, Fei; Ye, Song; Sun, Qianghu
ABSTRACT: Increasing evidence has reported that long non-coding RNA (lncRNA) plays a vital role in the development of pancreatic cancer (PC). However, the function and mechanism of LINC01133 in PC tumorigenesis are still unknown. Herein, we found that LINC01133 was highly expressed in PC tissues and cell lines, and LINC01133 knockdown could block the growth and metastasis of PC cells. Besides, upregulated LINC01133 in PC cells was induced by Yin Yang 1 (YY1) . Furthermore, LINC01133 directly targeted miR-199b-5p and promoted cancer malignancy by suppressing miR-199b-5p . It was also discovered that myelin regulatory factor (MYRF) was targeted by miR-199b-5p and positively correlated with LINC01133 expression in PC, and LINC01133 modulated PC progression through miR-199b-5p/MYRF pathway. In conclusion, we demonstrated that YY1 -mediated the upregulation of LINC0113 increased MYRF expression by sponging miR-199b-5p, resulting in the accelerated development of PC. These findings might offer a novel insight into the development of efficient therapeutics for PC patients. GRAPHICAL ABSTRACT: uf0001